2020
DOI: 10.1002/cpt.1957
|View full text |Cite
|
Sign up to set email alerts
|

MTXPK.org: A Clinical Decision Support Tool Evaluating High‐Dose Methotrexate Pharmacokinetics to Inform Post‐Infusion Care and Use of Glucarpidase

Abstract: Methotrexate (MTX), an antifolate, is administered at high doses to treat malignancies in children and adults. However, there is considerable interpatient variability in clearance of high‐dose (HD) MTX. Patients with delayed clearance are at an increased risk for severe nephrotoxicity and life‐threatening systemic MTX exposure. Glucarpidase is a rescue agent for severe MTX toxicity that reduces plasma MTX levels via hydrolysis of MTX into inactive metabolites, but is only indicated when MTX concentrations are … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 44 publications
(77 reference statements)
1
32
0
Order By: Relevance
“…In current study, SCr was identified as a statistically significant covariate on clearance of MTX, which corresponded with above studies. Moreover, a recent population PK model utilizing approximately 32,000 MTX concentration data from a large-scale pediatric patient population receiving MTX chemotherapy (Taylor et al, 2020) found a non-linear relationship between time-varying SCr and clearance. In the current study, we were unable to find a nonlinear relationship between time-varying SCr and clearance; this might be due to the narrow distribution of SCr and the small sample size compared to those of the previous study.…”
Section: Discussionmentioning
confidence: 99%
“…In current study, SCr was identified as a statistically significant covariate on clearance of MTX, which corresponded with above studies. Moreover, a recent population PK model utilizing approximately 32,000 MTX concentration data from a large-scale pediatric patient population receiving MTX chemotherapy (Taylor et al, 2020) found a non-linear relationship between time-varying SCr and clearance. In the current study, we were unable to find a nonlinear relationship between time-varying SCr and clearance; this might be due to the narrow distribution of SCr and the small sample size compared to those of the previous study.…”
Section: Discussionmentioning
confidence: 99%
“…PK findings from clinical studies can lead to improvements in therapeutic outcomes through amendments to clinical protocols [5,15] or the development of clinical decision support tools [16]. It was recently shown that >90% of persons have an actionable drug-gene polymorphism [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, population PK model of methotrexate was integrated into CDS tool which can be utilized to evaluate high exposure of methotrexate. Subsequently, this tool is able to inform the use of glucarpidase to reduce methotrexate plasma concentration ( 62 ).…”
Section: Resultsmentioning
confidence: 99%